Determinants of disruptive innovation that influences financial service performance - Khalifa Khalfan Muftah Al Mansoori; Mohammed Hariri Bakri (Global Business & Finance Review (GBFR), 2023)
Purpose: Disruptive innovation has been considered an important input to the economic growth of a business operation. Responding to the changing landscape towards disruptive innovation resulting from advanced technological development, the UAE government has started to focus seriously on the development of new disruptive technology platforms. Thus, as an initial step in developing a model of disruptive innovation factors that contributes to the financial service performance in the UAE, this study was geared towards investigating the disruptive innovation factors towards financial service performance. Design/methodology/approach: This research employed a quantitative research method. The data were collected from 315 respondents among executive banking officers at Mohammed Bin Rashid Centre for Government Innovation, in Abu Dhabi through questionnaires. Findings: The results indicated that disruptive innovation factors of financial service performance in the UAE showed a rather high level of technology intention towards innovation. As for the disruptive innovation factors, the economic, environmental and social were proven significantly and positively related to financial service performance. Therefore, the results supported Innovation Diffusion Theory and Technology Acceptance Model that both disruptive business models and disruptive technology influence a financial institution's performance. Research limitations/implications: This paper offers important implications specifically This study has successfully shed some light on the willingness of current disruptive innovation to transform into a financial service performance context. The result of this study suggested that every business leader is playing a crucial part in influencing others to take up disruptive innovation practices in business. Since financial institutions can only practice disruptive in- novation transition when the owner-managers appreciate it, it is therefore viable for the existing financial institution to share their own experiences or success stories with others. The government needs to have disruptive innovation since financial service performance is assumed to be a significant job and become an impetus of monetary and economic development in UAE, with the commitment of 80 percent of absolute innovation establishments in UAE that add to 20 percent of the nation's Gross Domestic Product (GDP), while shares 10 percent exports of the country. Concerning the national agenda vision 2021, the government aimed at becoming a high-income nation. Originality/value: The disruptive innovation factors can be a focus on economic, environmental, and social for enhancing a financial service performance. Yet, the integration of disruptive technology as cost-benefit, compatibility, and complexity in the relationship between a disruptive business model in the value proposition, resources accessibility, and business structure with disruptive innovation factors towards financial service performance.
Keywords: 650; Disruptive Innovation; Financial; Performance; Business Model; Diffusion Theory